1950
DOI: 10.1017/s0025315400055375
|View full text |Cite
|
Sign up to set email alerts
|

Gregariousness during settlement in the barnacle Elminius modestus Darwin

Abstract: A gregarious tendency during settlement, similar to that already demonstrated in oyster larvae, was suspected in Elminius, because cyprids settled in groups during the initial stages of colonization of surfaces (crowded later arrivals showed a spacing-out tendency) and because settlement on test-plates was peculiarly sparse at stations with a muddy bottom, where barnacles were absent.Settlement was much heavier on areas of smooth glass, which already bore recently settled barnacles, than on similar adjoining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 7 publications
0
57
0
Order By: Relevance
“…Even though the maximum potential length of the planktonic cyprid stage is a function of food reserves, its actual length will be determined by the availability of a surface for attachment, and in Balanus balanoides, Elminius modestus and several other species of barnacles settlement is enhanced by an aggregation or intraspecific response of larvae to resident juveniles or adult members of its own species (Knight-Jones and Stephenson, 1950;Knight-Jones, 1953;Crisp, 1963). Accordingly, the length of the cyprid stage in B. balanoides will vary from a few days up to a maximum of 5 wk, depending both on an encounter with a site suitable for settlement and upon the amount of energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the maximum potential length of the planktonic cyprid stage is a function of food reserves, its actual length will be determined by the availability of a surface for attachment, and in Balanus balanoides, Elminius modestus and several other species of barnacles settlement is enhanced by an aggregation or intraspecific response of larvae to resident juveniles or adult members of its own species (Knight-Jones and Stephenson, 1950;Knight-Jones, 1953;Crisp, 1963). Accordingly, the length of the cyprid stage in B. balanoides will vary from a few days up to a maximum of 5 wk, depending both on an encounter with a site suitable for settlement and upon the amount of energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-specific settlement responses are now well known for a number of invertebrate taxa. For example, it has been shown that cyprids of the barnacles Elminius modestus and Balanus balanoides settle gregariously in response to members of their own species (Knight-Jones and Stephenson, 1950;Knight-Jones, 1953), and veligers of oysters belonging to Ostrea edulis and Crassostrea virginica also settle in response to attached members of their own kind (Knight-Jones, 1951;Crisp, 1967;Bayne, 1969;Hidu, 1969). At least one serpulid polychaete (sensu stricto), namely Pomatoleios kraussi from the Arabian Gulf, probably also settles gregariously (Crisp, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae may transport to a 13 site, but a large portion may be preyed upon before settlement (Alfaro, 2006;Porri et al, 2008a), 14 and fewer larvae may settle in sites where there are no settlement cues (Knight-Jones and 15 Stevenson, 1950;Hills et al, 1998). Similarly, consistent temporal (seasonal, Bertness et al, 16 1992;Pineda, 1994a) and spatial variability in settlement among sites separated from meters to 17 tens of kilometers (Pineda, 1994a and pers.…”
mentioning
confidence: 99%
“…Knight-Jones and Stevenson, 1950;Kent et al, 2003) and intensification (Pineda, 1994a) implies 19 that individuals may realize higher population connectivity (measured, for example, as number 20 of individuals from site a and population A that disperse to site b, containing population B and 21 reproduce e.g., Pineda et al, 2007). This is because settling in high density and near settled 22 conspecifics results in more potential mates and enhanced reproductive potential.…”
mentioning
confidence: 99%